Testicular Function and Bone in Young Men with Severe Childhood-Onset Obesity - Laakso S; Viljakainen H; Lipsanen-Nyman M; Turpeinen U; Ivaska KK; Anand-Ivell R; Ivell R; Mäkitie O (S. Karger AG, 2022)
BACKGROUND:
Previous studies suggest increased risk for hypoandrogenism and fractures in men with obesity. We aimed to describe the effects of severe childhood-onset obesity on the cross talk between metabolic state, testes, and skeleton at late puberty.
METHODS:
A cohort of adolescent and young adult males with severe childhood-onset obesity (n = 21, mean age 18.5 years) and an age-matched control group were assessed for testicular hormones and X-ray absorptiometry-derived bone mass.
RESULTS:
Current median body mass indexes for the obese and control subjects were 37.4 and 22.9. Severe early-onset obesity manifested with lower free testosterone (median [interquartile range] 244 [194-332] vs. 403 [293-463] pmol/L, p = 0.002). Lower insulin-like 3 (1.02 [0.82-1.23] vs. 1.22 [1.01-1.46] ng/mL, p = 0.045) and lower ratio of testosterone to luteinizing hormone (2.81 [1.96-3.98] vs. 4.10 [3.03-5.83] nmol/IU, p = 0.008) suggested disrupted Leydig cell function. The degree of current obesity inversely correlated with free testosterone (τ = -0.516, p = 0.003), which in turn correlated positively with bone area at all measurement sites in males with childhood-onset obesity.
CONCLUSIONS:
Severe childhood-onset obesity is associated with impaired Leydig cell function in young men and lower free testosterone may contribute to impaired skeletal characteristics.